On the quantile past lifetime of the components of the parallel systems. Issue 7 (2nd April 2016) - Noughabi, M. Shafaei; Izadkhah, S.
ABSTRACT: Let T 1: n ⩽ T 2: n ⩽ ⋅⋅⋅ ⩽ T n : n be ordered lifetimes of components of a parallel system. In this article, the α-quantile past lifetime from the failure of the component with lifetime T r : n provided that the system has failed at or before time t has been introduced. Then, some properties of this measure have been studied.